Porajanje virtualnega globalnega trga in njegovi vplivi na mednarodni marketing - Jurše, Milan (Akademija MM, 1999)
In spite of the fact that current level of international trade on the internet is relatively low in comparison to conventional international trade, Internet represents one of the key emerging information technological innovations on the eve of 21st century, promissing to challenge traditional marketing concept, organisation of business processes and menedžerial concepts. Internet creates a new context for global virtual market, characterized by sovreign customer with easy access to market information and growing bargaining power against suppliers and distributors. Through these underlying changes a new marketing paradigm is emerging and through replacement of the conventional mass marketing concept with one-to-one marketing it relies upon marketing relationship development with each individual customer at once. Interactivity in relationship development with each customer supports strategic shift toward partnerships and more balanced division of power between suppliers and their customers aimed at realising a long-term profitability of these relationships. Internet creates new global market space with active consumers, who are becoming more sovereign market participants due to an unhindered access to market information and consequently, their bargaining power will be increased in the market exchange process. Traditional mass marketing concept will be gradually replaced by direct (one-to-one) marketing, based on interactive development of a firm's relationships with an individual customers and long-term relationships between suppliers and their customers. Internet represents not only a new type of distribution and communication channel, but also delineates profound changes in a basic marketing paradigm and enables also to SME to enter efficiently the global market. It changes the tarditional division of power between market participants in a way it enables customers to be well informed about the market and thus active and powerful subjects who enter well informed into the exchange process. Consequently, also geographic distance between markets are losing their traditional role as barriers to exchange in international marketing and with the emerging virtual global market new concepts for success in the market will replace traditional ones and conventional marketing principles will be changed or rewritten. Companies have the possibility to enter the global market efficiently through Internet and can use this new marketing infrastructure as a framework for active and aggressive development of future marketing and overall business startegies. In this new marketing environment and rules also Slovenian companies will have to encouraged to embed their marketing and business startegies more aggressively into the Internet context.
Keywords: elektronsko poslovanje; informacijska tehnologija; information technology; Internet; mednarodna trgovina; mednarodni marketing; mednarodno trženje; strategija trženja; svetovni trg